La Etnografía y el desarrollo social en el distrito de Laredo - Alvarez Barboza, Jerry Dante (2023)
Ethnography, within Anthropology, became the method par excellence in the description of social reality. The current importance has been recognized by all the social sciences and many of the basic sciences. In this work we intend to demonstrate that importance. The main objective of this document is to show how ethnography, as a research method, serves to recognize the main elements or potentialities of a social reality that serve as levers in social development. The main mechanisms of social analysis that have been used since the 80s with the boom of development projects, have seen their attempts to improve living conditions fail. This is due to a misdiagnosis of social reality. This work evidences the importance of the ethnographic method in the understanding of social reality